Theoretical characterization of the chemical bonds of some three-membered ring compounds through QTAIM theory - Duarte, Darío Jorge Roberto (2015)
Fil: Duarte, Darío Jorge Roberto. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.